Weber Syndrome Revisited: A Classic Midbrain Stroke Presentation Secondary to Severe Dyslipidemia - Adhalma Ciptaning Andarani Amalia; Harris Murdianto (HM Publisher, 2025)
Background: Weber syndrome is a classic brainstem stroke syndrome resulting from an ischemic lesion in the ventral midbrain. While historically defined by its striking clinical features—ipsilateral oculomotor nerve palsy and contralateral hemiparesis—its modern relevance lies in its direct causation by common, modifiable vascular risk factors. This report uses a quintessential case of Weber syndrome as a didactic tool to illustrate the profound microvascular consequences of a specific, severe metabolic phenotype. Case presentation: A 60-year-old female with a history of medication non-adherence for hypertension and hypercholesterolemia presented with acute left hemiparesis, right ptosis, and diplopia. Examination confirmed a right oculomotor palsy and left hemiparesis. Her Body Mass Index was 28.5 kg/m². Laboratory workup revealed a severe mixed dyslipidemia (LDL-C 168 mg/dL, Triglycerides 218 mg/dL). Brain MRI confirmed an acute infarct in the right ventral mesencephalon. Vascular imaging was unremarkable, pointing towards intrinsic small vessel disease. A comprehensive, multidisciplinary management plan was initiated, focusing on aggressive medical therapy, intensive rehabilitation, and strategies to overcome barriers to medication adherence. Conclusion: This case highlights the elegant yet unforgiving precision of neuroanatomy and the powerful diagnostic utility of modern neuroimaging. More profoundly, it demonstrates the direct pathophysiological link between severe atherogenic dyslipidemia and the occlusion of a single, critical perforating brainstem artery. The patient’s significant functional recovery underscores that a holistic approach—combining evidence-based pharmacotherapy with a robust, patient-centered rehabilitation program and a dedicated strategy to ensure long-term adherence—is paramount to optimizing outcomes after a debilitating stroke.